2007
DOI: 10.1002/rra.1022
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in macroinvertebrate communities of a heavy metal polluted stream: the river Nent (Cumbria, UK) after 28 years

Abstract: The macroinvertebrate fauna of the river Nent, a heavy metal polluted upland stream in northern England, first surveyed in 1976, was re-examined in 2004 to assess long-term changes in relation to activities in the catchment which have included, a river restoration project, works associated with the development of a mine heritage site and the removal of a chicken farm and more effective organic pollution control measures. The degree of change between years in total abundance, numbers of taxa and community compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(40 citation statements)
references
References 50 publications
(39 reference statements)
3
37
0
Order By: Relevance
“…India therefore faces a substantial challenge to meet the legal and moral obligations towards the provision of safe water [31]. Heavy metals are serious pollutants due to their toxicity, persistence in natural conditions and ability to be incorporated into food chains [52], [30], [7], [43]. Rapid urbanization and population growth in fast growing cities leading to industrialization poses a major threat of Heavy metal pollution for India's rivers flowing through these cities [50], [19], [04], [02].…”
Section: Introductionmentioning
confidence: 99%
“…India therefore faces a substantial challenge to meet the legal and moral obligations towards the provision of safe water [31]. Heavy metals are serious pollutants due to their toxicity, persistence in natural conditions and ability to be incorporated into food chains [52], [30], [7], [43]. Rapid urbanization and population growth in fast growing cities leading to industrialization poses a major threat of Heavy metal pollution for India's rivers flowing through these cities [50], [19], [04], [02].…”
Section: Introductionmentioning
confidence: 99%
“…Contaminated drainage from abandoned metal mines and mine spoil are issues of international concern that can severely impact hydrological (Grimshaw et al 1976;Gammons et al 2005), sedimentological (Macklin et al 2006;Dennis et al 2009) and ecological (Gower et al 1994;Armitage et al 2007) systems. The varied geology of the UK has provided many valuable natural resources and mineral exploration has occurred since the early Bronze Age (Environment Agency 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Clements et al (1992) also observed an increased abundance of Chironomidae taxa in the Clinch River in Virginia, which is severely polluted with heavy metals. Along-term study of the impact of heavy metals originating from a Zn and Pb mine on the macroinvertebrate community showed an increasing abundance of Chironomidae (Armitage et al 2007). Similar results were obtained by Canfield et al (2009) and Michailova et al (2012a).…”
Section: Discussionmentioning
confidence: 99%